N -haloacetyl phenothiazines and derivatives: Preparation, characterization and structure-activity relationship for antifungal activity - Sarmiento, Gabriela Pabla (2017)
A serie of N-acetyl phenothiazines and related compounds was synthesized by means of the acetylation reaction of the corresponding phenothiazine with the appropriate reagent using microwave irradiation. Structural elucidation of these heterocyclic derivatives was done using 1 H, 13C NMR spectra. The equilibra between conformationals enantiomers were studied as a possible atropisomerism case. The single crystal X-ray diffraction of some derivatives was also recorded and the presence of enantiomers could be confirmed. The antifungal activity evaluation of all N-acetyl phenothiazines prepared by us in this and in a previous work, was performed in vitro against 163 isolated human pathogenic yeasts and filamentous fungi, including: Cryptococcus neoformans, Candida albicans, Candida non-albicans, Aspergillus and Acremonium-Fusarium. The most promising compounds were those bearing one chlorine or bromine atom attached to the N-acetyl group. These compounds were as active as 5-fluorocitosine (5-FC) or fluconazole (FCZ), currently in clinical use. A structure-activity relationship (SAR) and a quantitative structure-activity relationship (QSAR) for antifungal activity of each genus were established.